ANTIOXIDANT ACTIVITY AND PHYSICAL PROPERTIES SOYGHURT EDAMAME WITH RED BEET - Diasari, Nur Reta; Nurrahman, Nurrahman; Yusuf, Muhammad (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2021)
Soyghurt is a soy milk product fermented by Lactobacilus bulgaricus and Streptococcocus thermopilus. Edamame soybeans are processed into yogurt with the addition of red beets which are good for health and rich in antioxidants. The purpose of this study was to determine the effect of adding beetroot on antioxidant activity and physical properties of edamame soyghurt. The stages of making soyghurt begin with making edamame soybean juice, adding red beet juice with a concentration of 0, 5, 10, & 15%, inoculating 7% of the yogurt starter culture, and incubating for 24 hours. The soygurt products produced were analyzed for their antioxidant activity and physical properties (pH, viscosity, total dissolved solids). The results showed that the addition of red beetroot to edamame soygurt had an effect on antioxidant activity, pH, viscosity, total dissolved solids, color and taste. The addition of beetroot increases the value of antioxidant activity, but decreases pH, viscosity, and total dissolved solids. The addition of 5% beetroot was the best treatment with antioxidant activity of 17.56%, viscosity of 4346 mPa.s, pH of 4.2, and total dissolved solids of 6.4oBrix.